Which predictors differentiate between obese children and adolescents with cardiometabolic complications and those with metabolically healthy obesity?. Issue 7 (13th June 2018) - Margolis‐Gil, Merav; Yackobovitz‐Gavan, Michal; Phillip, Moshe; Shalitin, Shlomit
Abstract : Background/Aims: Childhood obesity and associated metabolic comorbidities is a major global health concern. Metabolically healthy obesity (MHO) may represent a subgroup of individuals in which excessive body fat accumulation does not lead to adverse metabolic effects. We aimed to determine the prevalence of MHO among obese Israeli children and adolescents and to find predictors for metabolically unhealthy obesity (MUO). Methods: In a retrospective study, demographic, anthropometric, lifestyle, and cardiometabolic data were retrieved from medical records of patients with a body mass index (BMI) >95th percentile aged 6 to 17.6 years, attending a tertiary pediatric obesity clinic between 2008 and 2015, with at least 1 year of follow‐up. Participants were dichotomized as either MHO or MUO based on cardiometabolic risk factor clustering (blood pressure, serum lipids, and glucose). Multivariable logistic regression was used to determine predictors of MUO. Results: Of the 230 children (median age 9.9 years) fulfilling study criteria, 48 (20.9%) were classified as MHO. Occurrence of MUO was associated with male gender, Arabic ethnicity, higher BMI‐SD score, higher tri‐ponderal mass index (TMI), and higher insulin resistance (IR) (presence of acanthosis nigricans and a higher level of homeostasis model assessment‐IR [HOMA‐IR]). Male gender (odds ratio [OR] 2.27, P  = .033), presence of acanthosis nigricans at baseline (OR 2.35, P  = .035), and a greater increase in BMI‐SDS during follow‐up (OR 2.82, P  = .05) were the best predictors of MUO. Conclusions: The MHO phenotype was present in only 20.9% of obese Israeli children. MUO was significantly associated with male gender, with presence of acanthosis nigricans, and with a greater increase in BMI‐SDS during follow‐up.